Practical Marketing System as a Solution to Limited Labor and Post-Harvest Processing Areas for Rice - ARISENA, Gede Mekse Korri; DARMAWAN, Dwi Putra; SUKENDAR, Ni Made Classia; DEWI, Ni Luh Made Indah Murdyani; KRISNANDIKA, Anak Agung Keswari; DUNENSA, Dina Lare (Theoretical and Practical Research in Economic Fields, 2024)
The majority of rice farmers in Denpasar City chose a practical marketing system, this system implements rice sales based on estimated production results. Farmers generally sell their produce when the rice is approaching harvest time. The buyer determines the purchase price for rice by estimating the number of transaction objects after carefully observing and viewing the rice to be harvested. With this system, farmers no longer need to think about the availability of labor to harvest, transport the harvest home, dry the grain until it reaches a certain level of dryness. The novelty of this research is conducting in-depth research on the practice of buying and selling rice using a practical marketing system in Denpasar City. This research will also examine in depth the practical marketing system from two sides, namely from the perspective of farmers and buyers. The results of this research reveal that the practice of buying and selling rice using a practical marketing system in Denpasar City involves farmers as sellers and buyers who are usually called penebas. The reason why farmers choose a practical marketing system is that this system is considered more profitable for farmers with all the limitations of farming in urban areas, where farmers only need to care for the rice they plant until it is ready to harvest .